Cинтез новых производных серосодержащих вицинальных аминоспиртов на базе N-(оксиран-2-илметил)аминов - А. С. Галстян; Э. Г. Месропян (ՀՀ ԳԱԱ հրատ.)
Взаимодействием N-(оксиран-2-илметил)аминов с метиловым эфиром меркаптоуксусной кислоты получены метиловые эфиры 2-(3-(N,N-дизамещенных)амино-2-гидроксипропилтио)уксусной кислоты. Последние обработкой аммиаком и пероксидом водорода переведены в новые производные сульфоксидов, содержащих аминоспиртовую и амидную группы. N-(Օքսիրան-2-իլմեթիլ)ամինների փոխազդեցությունից մերկապտոքացախաթթվի մեթիլէսթերի հետ սինթեզվել են մեթիլ 2-(3-(N,N-դիտեղակալված)ամինո-2-հիդրօքսիպրոպիլթիո)ացետատներ, որոնց հետագա մշակումը ամոնյակով և ջրածնի պեռօքսիդով բերում է ամինասպիրտային և ամիդային խմբավորումներ պարունակող սուլֆօքսիդների նոր ածանցյալների ստացման: The purpose of this paper is the design of new molecules containing amide, sulfoxide, amino alcohol groups to create new pharmaceuticals. To achieve the goal the interaction of N-(oxirane-2-ylmethyl)amines with methyl 2- mercaptoacetate was carried out, which resulted in methyl 2-(3-(N,N-disubstituted) amino-2-hydroxypropylthio) acetates. The latter being processed with ammonia and hydrogen peroxide were transferred into new sulfoxides derivatives containing amino alcohol and amide groups. Based on the NMR spectra it can be stated that due to oxidation sulfoxides formed rather than sulfones because the sulfoxide group is a chiral center of the multiplet structure.
Keywords: Biochemistry; Organic Chemistry